Respostas

2014-02-06T16:42:21-02:00
Primeiro descubra x, y e z
          
x= 2° - 3 -¹      x=1- (1/3)¹    x = 1- 1/3     x = 3 - 1    x = 2
                                                                    3            3    

y= 5° - 2 -¹      y=1- (1/2)¹    y = 1- 1/2     y = 1- 1     y = 0     y = 0
                                                                   2             2              

z= 4° + 4 -¹    z=1- (1/4)¹    z = 1 + 1/4     z = 4 + 1    z = 5
                                                                     4             4
           

a) x+y =   2/3 + 0  = 2/3


b) x-y  =  
2/3 - 0  = 2/3 


c) x.y  = 2/3 * 0  = 0